Diurnal Variability in Reflectance Measurements from Cotton. Issue 4 (1st July 2014) - Oliveira, Luciane F.; Scharf, Peter C.
ABSTRACT: Diurnal variability of reflectance measurements on crop plants has been documented for passive sensors, but minimally studied for active sensors. Active sensors are now commercially available for crop management decisions including diagnosis and control of N rate. Our objective was to quantify variability during the day for both passive and active sensors mounted above a cotton canopy, and to assess the effect that this variability would have on N rate decisions. Measurements were taken from 0600 to 2000 h at early square, midsquare, and early flower growth stages using Cropscan (passive), Crop Circle (active), and GreenSeeker (active) reflectance sensors. Average CV for GreenSeeker was higher than for Crop Circle for visible/near‐infrared (Vis/NIR) ( P = 0.01) and possibly for normalized difference vegetative index (NDVI) as well ( P = 0.15). Variability in Cropscan reflectance was much higher in north‐south than in east‐west rows. When restricted to east‐west rows, Cropscan CVs were equal to or lower than the other sensors. Nitrogen rates calculated from sensor measurements also were more variable for GreenSeeker (SD ≥ 19 kg N ha –1 ) than for Crop Circle (SD ≥ 12 kg N ha –1 ) ( P < 0.09). GreenSeeker NDVI followed a consistent diurnal pattern: lower in midday and higher in morning and evening. A regression equation using temperature, solar radiation, and solar time explained 45 to 50% of this variability, and could potentially be used to correct values during field use. Additional study to isolate causal factors of variability is justified. Strategies to compensate for drift in reflectance measurements will be needed when using sensors to control applications of N fertilizer or other inputs, even for active sensors.